The Influence of a Specific Sprint Resisted Swimming Training Programme on the Intra-cyclic Velocity Variation of Young Female Front Crawl Swimmers - Ioannis K. Valkoumas; Vassilios Gourgoulis (Central European Journal of Sport Sciences and Medicine)
The aim of the current study was to investigate the effect of an 11-week sprint resisted swimming training programme on the front crawl mean swimming velocity and the intra-cyclic velocity variation (IVV). Twelve female swimmers assigned into an experimental (N= 6) and a control group (N= 6) followed the same training programme including a specific sprint protocol. The only difference between the two groups was the use of a swimming parachute from the experimental group during the specific sprint protocol. A 50 m maximal intensity front crawl trial, before and after the 11-week intervention period, was recorded by 4 digital video cameras. The Ariel Performance Analysis System was used for the digitization of selected anatomical landmarks and two-way repeated measures ANOVAs were performed for the statistical treatment of the data. After the intervention programme, the experimental group showed a significant increase in the mean swimming velocity, the stroke rate, the propulsive phase duration and the index of coordination, and a significant decrease in the non-propulsive phase duration, the total stroke duration and the IVV. These modifications could be considered a positive effect, helping the swimmers to become more efficient to overcome the inertial forces and to improve their swimming performance.